A Review on Heat Transfer Enhancement Using Magnetic Nanofluids - Hussain, Taliv; Javed, Mohammad T.; Ansari, Raquib Imam (Nanoscience & Nanotechnology-Asia, 2020)
Magnetic nanofluids are defined as fluids exhibiting magnetic properties. These fluids are generated by suspending nanoparticles of magnetic nature in any base fluids. Magnetic nanofluids have been a topic of interest for researchers because of their highly useful and manipulatable properties. With the use of these fluids, heat transfer and flow characteristics can be controlled by applying external magnetic fields. This paper reviews recent investigations in the field of magnetic nanofluids with the purpose of assessing the effects of various parameters on their heat transfer and flow characteristics. The objective of this review is to study the research done in this field and understand the level at which this technology stands with all its opportunities and challenges. The review has been classified into experimental and numerical simulation work. Investigations in the presence and absence of magnetic field have been discussed under experimental work. Investigations in the domain of numerical simulation of magnetic nanofluids have been classified into single phase and multiphase analysis. Some novel applications of magnetic nanofluids have also been discussed. It has been concluded that research in the field of magnetic nanofluids is still in the preliminary stages and further experimental and simulation work needs to be done. The physical process needs to be understood with a deeper perspective to create better models for simulation. In spite of the challenges, research in this field of study has given exciting results and it holds vast potential applications.
Keywords: metals